The Audit’s Subject Matter and the Auditor’s Opinion: Selection of an Audit - Nina K. GOGOLL (Communications of International Proceedings, 2021)
Through the auditing of annual financial statements, auditors comply with governmental standards and with the auditor’s opinion a certain quality evaluation is demonstrated to the public. The auditing is useful for the stakeholders’ interest. However, disclosed and published corporates fraud cases are often connected with the auditor’s failure in the public mind. Therewith the research questions respectively interest have evolve about the subject matter of the audit, the auditors function referring to the going concern and fraud as well as the content of the auditor’s opinion. In order meet that request this article follows the methodology of the formal-analytical research strategy with the simple and more or less abstract describing of problem structures (cp. Grochla, 1978, p. 85) by introducing the problem of the public impression of auditor’s failure. This is complemented by the secondary research method by researching and checking governmental laws. The finding is that from the legal aspect the responsibility of a corporate’s financial statement, the going concern and fraud are in charge of the legal corporate’s representatives. The auditor’s opinion bases on the corporate information and for this reason the audit contains issues which are provided by a corporate’s management.
Keywords: Audit; Audit’s Subject Matter; Auditor’s Opinion.